2017
DOI: 10.1248/cpb.c16-00513
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Solubility and Oral Bioavailability of Poorly Water-Soluble Drugs Using Monoolein Cubosomes

Abstract: Monoolein cubosomes containing either spironolactone (SPI) or nifedipine (NI) were prepared using a high-pressure homogenization technique and characterized in terms of their solubility and oral bioavailability. The mean particle size, polydispersity index (PDI), zeta potential, solubility and encapsulation efficiency (EE) values of the SPI-and NI-loaded cubosomes were determined to be 90.4 nm, 0.187, 13.4 mV, 163 µg/mL and 90.2%, and 91.3 nm, 0.168, 12.8 mV, 189 µg/mL and 93.0%, respectively, which were almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
(35 reference statements)
0
27
0
Order By: Relevance
“…Moreover, when considering the delivery of hydrophobic drugs, such as AT101, the benefit of using cubosomes is the improvement in the bioavailability of the drug due to its greater solubility in the lipid membrane of formed nanoparticles and finally their dispersion in water-based media. A similar approach to enhancing the solubility and, hence, the bioavailability of hydrophobic drugs by using monoolein-and phytantriol-based cubosomes was described by Ali et al 50,51 The improved cytotoxicity response to GMO-AT101 cubosomes can be further related to the pronounced internalization associated with endocytic pathways, as reported previously by Abdel-Bar et al ( Figure 6). 47 Moreover, AT101 molecules exhibit a high binding affinity to proteins resulting in a reduced AT101 activity.…”
Section: Encapsulated At101 Exhibits Stronger Cytotoxic Effects and Mmentioning
confidence: 57%
“…Moreover, when considering the delivery of hydrophobic drugs, such as AT101, the benefit of using cubosomes is the improvement in the bioavailability of the drug due to its greater solubility in the lipid membrane of formed nanoparticles and finally their dispersion in water-based media. A similar approach to enhancing the solubility and, hence, the bioavailability of hydrophobic drugs by using monoolein-and phytantriol-based cubosomes was described by Ali et al 50,51 The improved cytotoxicity response to GMO-AT101 cubosomes can be further related to the pronounced internalization associated with endocytic pathways, as reported previously by Abdel-Bar et al ( Figure 6). 47 Moreover, AT101 molecules exhibit a high binding affinity to proteins resulting in a reduced AT101 activity.…”
Section: Encapsulated At101 Exhibits Stronger Cytotoxic Effects and Mmentioning
confidence: 57%
“…Sustained release of caffeine may be useful to have alertness longer than the 3 or 4 h corresponding to immediate absorption. A consequence of the controlled release property is that lipidic lyotropic liquid crystalline phases can also be used for amphiphilic and lipophilic substances to increase bioavailability, which is the amount of an active substance, which reaches the plasma after transiting the digestive tract and being absorbed across the gastro‐intestinal barrier. For tocopherol vitamin, for instance, it was demonstrated that the L 1 phase, composed of micelles of positive curvature, made with polysorbate, leads to higher vitamin absorption than commercial soft gel capsules .…”
Section: Technological Applications Of Lipidic Lyotropic Liquid Crystmentioning
confidence: 99%
“…Studies have shown that GMO cubosomes improve the efficiency of AmB via the oral route [53]. On the other hand, monoolein cubosomes enhance the oral bioavailability and solubility of poorly water-soluble drugs [54]. Recent studies have been shown that cubosomes act as efficient oral drug delivery systems in enhancing the release of clopidogrel bisulphate in the intestine [55].…”
Section: Nanostructures For Drug Delivery By Oral Administrationmentioning
confidence: 99%